Gambaran Histologi Insang Ikan Mas Koki (Carassius auratus) yang Terinfeksi Ektoparasit Argulus sp. - Rifqiyati, Najda; Miftah, Atika Nurul; Luthfi, M. Ja’far (bionature, 2017)
Fantail goldfish (Carassius auratus) was interested in the fans fish.The cultivation of fantail goldfish needs to vigilance against the parasite, especially Ectoparasite. Ectoparasite that attacks gills can cause death acute. This research attempts to compare structure histology damage gills of fantail goldfish (Carassius auratus) that was attacked by Argulus sp. seen from the time of infection and to see how long infection of Argulus sp. which causes damage on the gills. The research started from March-April 2016 at Department of Cangkringan Fisheries, Sleman and veterinary medicine laboratory of UGM. The research had been used of the artificial infection. The collection of the fish sample start from zero days (not infected), 1st, 2nd, and 3rd. the parameter that observed is the changes of macroscopic which includes clinical symptoms, the change of morphological body of the fish and gills change. In addition, the change of structure gills histology had to compare the level of damage to the making of prepared. The research result showed the change of macroscopic as symptoms clinical of the fish like passive swimming, appetite down and always rubbed the body at the aquarium. The change of morphological body of the fish as foul fins, injury of the skin and the growing of secondary parasite on the skin fish. As macroscopic gills also rose-colored blackish. The change of structure gills histology which infected by Argulus sp. is hyperplasia, congestion, and necrosis. On the first day of hyperplasia and necrosis, day 2 and 3 experienced hyperplasias, congestion, and necrosis with the highest severity on day 3. Environmental factors such as DO, pH, and temperature were unchanged for 3 days of trial and had no effect on Argulus sp. infection in the gills of the goldfish. Keywords: Argulus sp., ectoparasite, fantail goldfish (carassius auratus), histology, gills.